Пропозиції щодо оцінювання компетентності аудиторів систем управління інформаційною безпекою - Пашкова, А. В. (ХНУРЕ, 2024)
The work is devoted to the actual problem of assessing the consistency of experts' opinions in the field of information security. The work provides proposals for assessing the agreement of experts' opinions using the concordance coefficient, which takes into account the ranking of factors and provides a more accurate assessment of agreement than other methods.
Keywords: управління інформаційною безпекою; оцінювання компетентності аудиторів